Brief assessment of food insecurity accurately identifies high-risk US adults. Issue 8 (20th February 2017) - Gundersen, Craig; Engelhard, Emily E; Crumbaugh, Amy S; Seligman, Hilary K
Abstract: Objective: To facilitate the introduction of food insecurity screening into clinical settings, we examined the test performance of two-item screening questions for food insecurity against the US Department of Agriculture's Core Food Security Module. Design: We examined sensitivity, specificity and accuracy of various two-item combinations of questions assessing food insecurity in the general population and high-risk population subgroups. Setting: 2013 Current Population Survey December Supplement, a population-based US survey. Subjects: All survey participants from the general population and high-risk subgroups. Results: The test characteristics of multiple two-item combinations of questions assessing food insecurity had adequate sensitivity (>97 %) and specificity (>70 %) for widespread adoption as clinical screening measures. Conclusions: We recommend two specific items for clinical screening programmes based on their widespread current use and high sensitivity for detecting food insecurity. These items query how often the household 'worried whether food would run out before we got money to buy more' and how often 'the food that we bought just didn't last and we didn't have money to get more'. The recommended items have sensitivity across high-risk population subgroups of ≥97 % and a specificity of ≥74 % for food insecurity.